The Influence of Accounting Students' Understanding in Facing the Fundamentals of Accounting Course (Study on D3 and S1 Accounting Students of Bina Sarana Informatika University (UBSI) Surakarta - Wawan Haryanto (Mandalika Journal of Business and Management Studies, 2023)
The purpose of this research is to test the influence of understanding on the ability of students from SMA, SMK and Aliyah to understand Introduction to Accounting on students graduating from SMA. SMK, and aliyah as independent variables, while the dependent variables are assets, liabilities and capital. The data collection technique in this research is using a questionnaire, which is the population and sample in the research of 201 students in the first, third and fifth semesters of 2023/2024, Department of Accounting Information Systems and Information Systems Department. Hypothesis Regression Analysis in research on assets that influence high school students is 0.205 with a t count of IDR 0.3485 with a sig value of 0.001 so it can be concluded that high school graduate students understand from studying economics the influence of understanding obligations on vocational school students. Hypothesis in research on obligations that influence vocational school students leve of significant 0.469 with a calculated t of 10.932 with a Sig value of 0.000. Conclusion: Vocational school graduate students understand accounting obligations better in accounting because they have knowledge of honest accounting. Influence of Understanding Capital for High School, Middle School, Aliyah Students. Hypothesis in capital/equity research Influences Aliyah students for The regression coefficient is 0.8 with a t count of 0.15,400, a sing level of 0.000. Conclusion: Graduate students from aliyah receive social studies lessons. Meanwhile, for the F test, the influence of understanding assets influences SMA, SMK, Aliyah students with a sig of 0.001, so it can be concluded that high school graduate students understand from studying Economics, while for the F test it is partial and simultaneous significant relatinship is significantly 0,001 for R2 the adjusted to 39.9.% It can be concluded that SMA, SMK Aliyah funds are 39.9%. The remaining amount is 60.1%. Capital, assets, liabilities.